Invigorating Prescribed Fire Science Through Improved Reporting Practices - Bonner, Sophie R.; Hoffman, Chad M.; Kane, Jeffrey M.; Varner, J. Morgan; Hiers, J. Kevin; O’Brien, Joseph J.; Rickard, Heather D.; Tinkham, Wade T.; Linn, Rodman R.; Skowronski, Nicholas; Parsons, Russell A.; Sieg, Carolyn H. (Frontiers in Forests and Global Change, 2021)
Interest in prescribed fire science has grown over the past few decades due to the increasing application of prescribed fire by managers to mitigate wildfire hazards, restore biodiversity, and improve ecosystem resilience. Numerous ecological disciplines use prescribed fire experiments to provide land managers with evidence-based information to support prescribed fire management. Documenting variation in the context and conditions during prescribed fires as experimental treatments is critical for management inference, but inconsistencies in reporting critical experimental details can complicate interpretation. Such details are needed to provide ecological and empirical context for data, facilitate experimental replication, enable meta-analyses, and maximize utility for other scientists and practitioners. To evaluate reporting quality in the recent literature, we reviewed 219 prescribed fire experiments from 16 countries published in 11 refereed journals over the last five years. Our results suggest substantial shortcomings in the reporting of critical data that compromise the utility of this research. Few studies had specific information on burning conditions such as fuel moisture (22%), quantitative fuel loads (36%), fire weather (53%), and fire behavior (30%). Further, our analysis revealed that 63% of the studies provided precise coordinates for their study area, while 30% of studies indicated the prescribed fire date. Only 54% of the studies provided descriptions of the ignition characteristics. Given these common deficiencies, we suggest minimum reporting standards for future prescribed fire experiments. These standards could be applied to journal author guidelines, directed to researchers and reviewers by the editor, and promoted in the education of fire ecologists. Establishing reporting standards will increase the quality, applicability, and reproducibility of prescribed fire science, facilitate future research syntheses, and foster actionable science.